Methanol production from CO2: Via an integrated, formamide-assisted approach - Uranga, Jorge Gustavo (2020)
The synthesis of fuels from CO2 has made tremendous progress in recent years, although practical applications remain limited. Herein, we describe a cyclic process that produces MeOH from CO2via formamide intermediates, which are initially reduced using NaBH4 to form methanol and concomitantly release the corresponding amine, from which the formamide is subsequently regenerated in the presence of CO2/NaBH4. By tuning the substituents on the formamide/amine, the selectivity of both steps can be controlled, allowing the process to proceed in high yields, either in two separate steps or in a single step process. The observed trends in reactivity were rationalized with a resonance model of the formamide, which supports the observed trends in reactivity, and further consolidated by spectroscopy and calculations.